A free-form lensing model of A370 revealing stellar mass dominated BCGs, in Hubble Frontier Fields images. Issue 4 (9th October 2017) - Diego, Jose M.; Schmidt, Kasper B.; Broadhurst, Tom; Lam, Daniel; Vega-Ferrero, Jesús; Zheng, Wei; Lee, Slanger; Morishita, Takahiro; Bernstein, Gary; Lim, Jeremy; Silk, Joseph; Ford, Holland
Abstract: We derive a free-form mass distribution for the unrelaxed cluster A370 ( z = 0.375), using the first release of the Hubble Frontier Fields images (76 orbits) and GLASS spectroscopy. Starting from a reliable set of 10 multiply lensed systems, we produce a free-form lens model that identifies ≈80 multiple images. Good consistency is found between models using independent subsamples of these lensed systems, with detailed agreement for the well-resolved arcs. The mass distribution has two very similar concentrations centred on the two prominent brightest cluster galaxies (or BCGs), with mass profiles that are accurately constrained by a uniquely useful system of long radially lensed images centred on both BCGs. We show that the lensing mass profiles of these BCGs are mainly accounted for by their stellar mass profiles, with a modest contribution from dark matter within r < 100 kpc of each BCG. This conclusion may favour a cooled cluster gas origin for BCGs, rather than via mergers of normal galaxies for which dark matter should dominate over stars. Growth via merging between BCGs is, however, consistent with this finding, so that stars still dominate over dark matter. We do not observe any significant offset between the positions of the peaks of the dark matter distribution and the light distribution.